MODERN SPECIFICITY OF THE ORGANIZATION OF THE EDUCATIONAL PROCESS FOR APPLIED PHYSICAL CULTURE IN THE UNIVERSITY - Zaitseva, I.P. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to consider the problematic aspects and ways to solve them in the organization of the educational process in the discipline "Applied Physical Education" (elective disciplines), the implementation of which is carried out in accordance with the requirements of the current federal state educational standards of higher education. Methods and structure of the study. In the course of the study, an analysis and generalization of scientific and methodological literature on the research problem was carried out; generalization of pedagogical experience; the data of a sociological survey of students on self-study in applied physical culture of students of the 1st-3rd courses of all faculties and different specialties of P.G. Demidov Yaroslavl State University. Results and conclusions. The author notes that the right of educational organizations to make an independent decision on the implementation of physical culture and sports programs was the reason for the distribution of hours not for compulsory classes, but for independent work of the student. This leads to the fact that students do not study, and only a small percentage of them continue to regularly attend sports sections during their studies. As other problematic aspects, the author cites an inconvenient schedule of classes, the lack of logistical capabilities to create the required number of sections for sports. As conclusions, the author suggests ways to solve the problem of systematic physical activity by university students.